Why now? Delayed drug-induced pancreatitis due to dapsone for dermatitis herpetiformis - Youssef Yousry Soliman; Megan Sue Soliman; Farrukh Abbas (Journal of Community Hospital Internal Medicine Perspectives, 2018)
Drug-induced pancreatitis can be caused by a wide array of medications. In fact, the diagnosis is likely commonly missed due to the difficulty in diagnosing one agent as the sole cause. We present a case of dapsone-induced pancreatitis in a 75-year-old male with history of celiac disease. He presented with abdominal pain and was found to have acute pancreatitis. Interestingly, he had been on dapsone for 5 years and had no other recent medication changes, significant alcohol use, or gallbladder disease. It was determined this was an episode of delayed acute pancreatitis due to dapsone. This is a rarely addressed entity in the literature and is the first case in which pancreatitis occurred so late in a patient’s treatment course on dapsone.